Smile challenger - Ang, Shi Chao (2017)
A smile is a form of facial expression that are normally closely associated with happiness. Given that a smile can be measured, can we measure happiness and turn it into a fun Smile Challenger game? This paper presents an efficient approach to analyze a smile and assign a reasonable score (0 – 100%) to it.